Effective orifice diameter: a new sizing parameter of surgical valve prostheses to inform valve selection - Wu, Changfu; Green, Chad; Marquez, Salvador; Monelli, Paolo; Weinberg, Craig; Weston, Matthew; Lawford, Patricia; Cameron, Duke; Yoganathan, Ajit; Steinseifer, Ulrich (Annals of Cardiothoracic Surgery, 2024)
Background: The labeled sizes of surgical valve prostheses and their discordance with the physical internal valve orifice sizes has long been a controversy in the cardiac surgery community, leading many to believe it to be a contributing factor in prosthesis-patient mismatch following valvular replacement surgery. In an attempt to address this issue, the International Organization for Standardization (ISO) 5840-2:2021 standard for surgical valve prostheses recommends that a new sizing parameter, namely, the effective orifice diameter, be provided in labeling by all manufacturers as an indicator of the true flow-passing capacity of a prosthetic valve. Methods: The ISO Cardiac Valves Working Group conducted a multi-laboratory round-robin study to investigate whether the effective orifice diameter of a prosthetic surgical valve could be derived repeatably and reproducibly through steady forward-flow testing. A total of 7 valve models, each with multiple sizes, were tested, including a mechanical heart valve and multiple biological heart valves. Results: The round-robin study confirmed that the steady forward-flow test had good intra-laboratory repeatability and inter-laboratory reproducibility in deriving the effective orifice diameters of surgical valve prostheses. On average, among the participating laboratories, the experimentally derived effective orifice diameter of a prosthetic heart valve was 3–12 mm smaller than its labeled size. Conclusions: The effective orifice diameter provides better characterization of the hydrodynamic characteristics of a surgical valve prosthesis and can be derived using a validated steady forward-flow test method. This new sizing parameter will soon be adopted by surgical valve manufacturers and provided in device labeling to inform valve selection by surgeons.